2022
DOI: 10.7759/cureus.20961
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Risk of Surgery Following First Diagnosis of Benign Prostatic Hyperplasia in Middle-Aged Men

Abstract: Pharmacotherapy is often used to relieve lower urinary tract symptoms (LUTS) due to benign prostatic hyperplasia (BPH), yet surgery may be indicated for persistent bothersome symptoms. BPH is common among older men, yet the burden of BPH among middle-aged men may be under-recognized. This study examined the 5-year risk of BPH surgery among middle-aged men following the first BPH diagnosis. MethodsUsing the IBM MarketScan Commercial Claims and Encounters Database, males aged 35 to 64 years with a first-time pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…In this study (over a 24 month follow up period) 56 patients (56%) were found to have required or had prostatectomy. The higher percentage requirement for BPH surgery in this study could be due to the fact that the risk for BPH surgery may be underappreciated in the previous study as opined by the authors or the mean age in this study being higher than the study by [23] (64 years versus 54 years). Old age has been found to be an independent predictor of the risk for BPH surgery [23].…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In this study (over a 24 month follow up period) 56 patients (56%) were found to have required or had prostatectomy. The higher percentage requirement for BPH surgery in this study could be due to the fact that the risk for BPH surgery may be underappreciated in the previous study as opined by the authors or the mean age in this study being higher than the study by [23] (64 years versus 54 years). Old age has been found to be an independent predictor of the risk for BPH surgery [23].…”
Section: Discussioncontrasting
confidence: 51%
“…Reference [23] in a study in 4,510 men with first time primary diagnosis of BPH followed up over a 5-year period on medical therapy found that 460 men (10.2%) had BPH surgery. In this study (over a 24 month follow up period) 56 patients (56%) were found to have required or had prostatectomy.…”
Section: Discussionmentioning
confidence: 99%